Integrated nutrient management in onion and garlic - Thangasamy, A; Khade, Yogesh P; Godkhe, Pranjali H (Indian Horticulture, 2019)
Onion and garlic are important vegetable crops grown in India. Intensivecultivation with unbalanced application of N, P and K fertilizers alone tosoil has resulted in deterioration of soil health and stagnation in cropproductivity. Whereas, integrated use of plant nutrients through mineralfertilizers, organic manures and biofertilizers improves soil health and yieldof onion and garlic. Integrated nutrient management (INM) system is anecologically, socially and environmentally viable approach.